Molecular phylogeny and morphology reveal a new wood-inhabiting fungal species, Vararia tuberculata (Peniophoraceae, Russulales) from China - Wang, Kaisheng; Deng, Yinglian; Zhu, Yonggao; Chen, Meng; Zhao, Changlin (Phytotaxa, 2026)
Vararia is a species-rich genus in the family Peniophoraceae and is polyphyletic. In this study, a new species, Vararia tuberculata, is proposed based on a combination of morphological features and molecular evidence. It is characterized by membranous, adnate basidiomata with tuberculate, white to cream, isabelline to slightly brown hymenial surface, a dimitic hyphal system with generative hyphae bearing simple septa, cylindrical, subulate, and cylindrical to bottle-shaped cystidia, cylindrical basidia with 4-sterigmata, and fusiform basidiospores measuring 13.5–15.1 × 4.0–5.0 µm. The phylogenetic tree inferred from ITS+nLSU sequences reveals that Vararia tuberculata is nested within the family Peniophoraceae (Russulales), where it forms a sister species to V. cremea and V. gillesii. A full description, illustrations, and phylogenetic analysis results of the new species are provided.